Hepatitis Lupus in Systemic Lupus Erythematosus in Male Patients - Putra, Andikha; Raveinal (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease characterized by autoantibodies against the cell nucleus and involves many organ systems in the body with unknown etiologies and various clinical manifestations, disease course and prognosis. SLE can be found at all ages, generally appearing at age 9-58 years with a peak at age 28 years. It is more common in women with a ratio of women to men 15: 1 to 22: 1. The highest incidence and prevalence of SLE was found in North America 23.2 / 100.000 population / year and 241 / 100.0000 population. In Indonesia, there has been an increase in visits to SLE patients from 17.9-27.2% in 2015 to 30.3-58% in 2017. One of the manifestations of SLE is hepatitis lupus, which is inflammation of the liver tissue. Lupus hepatitis can occur in 20-50% of patients with SLE. It was reported that a 20-year-old man presented with complaints of pain in the joints of the right and left hands which increased since 1 week. The patient also complained of reddish patches on the face, hair loss and mouth sores. Physical examination revealed anemic eye conjunctiva, malar rash, oral ulcer. During the joint examination, there was tenderness in bilateral MCP and PIP. The abdominal examination revealed hepatomegaly. Investigations revealed anemia, thrombocytopenia, increased liver function. Abdominal ultrasound revealed hepatomegaly. ANA profile examination was positive for anti RNP, anti-sm, and anti- ribosomal protein antibodies. The patient was diagnosed with Systemic Lupus Erythematosus with lupus hepatitis according to the ACR (American College of Rheumatology) criteria in which the patient had 6 criteria. The patient was given therapy with 2x125 mg of intravenous methyl prednisolone for 3 days and hydroxychloroquine 1x200 mg orally and other symptomatic drugs.